Checklist of Dinotrema Foerster, 1863 species of Finland (Hymenoptera, Braconidae, Alysiinae) - Koponen, Martti; Peris-Felipo, Francisco Javier (Zootaxa, 2016)
In the present study, a total of 91 species of the genus Dinotrema Foerster, 1863 (Hymenoptera: Braconidae: Alysiinae) from Finland are catalogued. Of them, 73 species are recorded for the first time for this country. A faunistic list with distributional data and host records is provided.